Subjectivation, togetherness, environment. Potentials of participatory art for Art Education for Sustainable Development (AESD) - Illeris, Helene (Nordic Journal of Art & Research, 2017)
Through a process-oriented analysis of the participatory art project The Hill this article explores the relevance of participatory art projects for the development of AESD – Art Education for Sustainable Development. Inspired by Felix Guattari’s Three Ecologies (2008) the analysis moves through three sub-studies delving into three different aspects of the project. Each sub-study adopts two overlapping analytical ‘lenses’: The lens of a contemporary art form (performance art, community art, and site-specific art) and the lens of a related theoretical concept (subjectivation, togetherness, environment). The aim is to propose art educational ideas and strategies that stimulate students to challenge the current political, economic and environmental situation. Central questions addressed by the article are: How can educators use contemporary artistic strategies to challenge essentialist and opportunistic self-understandings? What is the potential for participatory art forms to explore alternative and more sustainable conceptions of human subjectivity? How can art education work in favour of a sense of interconnectedness between the individual, the social and the environmental dimensions of being? In conclusion, the article proposes art education as a symbolic place for carrying out art-inspired experiments with how to live our lives in more sustainable ways.